Organic room temperature phosphorescence co‐crystal with reversible acid/base stimulus response - Zhang, Chenchen; Jiang, Xingjia; Wang, Can; Liu, Zhaoyang; Xu, Bin; Tian, Wenjing (Smart molecules (Print), 2025)
Stimulus‐responsive organic room temperature phosphorescent (RTP) materials have received significant attention in bioimaging, sensing, and data storage because of their controllable dynamic variability and rapid response. Organic co‐crystals, with tailor‐designed optical properties through manipulation of their aggregate structures, have proven to be very effective in elucidating the structure‐property relationship of organic RTP materials at the molecular level. Therefore, enhancing RTP through rigid frameworks that promote intersystem crossing is a valid approach. Notably, the realization of organic RTP co‐crystal performance by altering the components or adjusting the crystal lattices is highly appealing; however, this has not been fully addressed. In this study, an organic RTP co‐crystal, 4,4′‐bipyridine (44BD), was employed as the host, and 1,4‐diiodotetrafluorobenzene (DITF) and 4‐bromo‐2,3,5,6‐tetrafluorobenzoic acid (TFBA) were employed as guests. The 44BD‐DITF co‐crystal exhibited an orange RTP, whereas 44BD‐TFBA displayed a bright yellow RTP. Crystal analysis and theoretical calculations revealed that dense molecular packing and abundant intermolecular interactions within these co‐crystals are crucial for the emergence of RTP. Notably, both co‐crystals show a reversible acid/base stimulus response, that is, exposure to hydrochloric acid (HCl) fumes results in quenching of their RTP, which can be subsequently restored by triethylamine (TEA) fumigation. This study presents an effective approach towards reversible RTP switching in organic co‐crystals, thus offering opportunities for the development of acid/base stimulus‐responsive materials for next‐generation applications.